Coincidence of Tethered Cord, Filum Terminale Lipoma, and Sacral Dural Arteriovenous Fistula: Report of Two Cases and a Literature Review - Przepiórka, Łukasz; Kunert, Przemysław; Juszyńska, Paulina; Zawadzki, Michał; Ciszek, Bogdan; Głowacki, Mariusz; Marchel, Andrzej (Frontiers in Neurology, 2018)
Abstract Spinal dural arteriovenous fistula (SDAVF) is the most common vascular malformation of the spine in adults. However, the coincidence of tethered cord syndrome, lipoma, and SDAVF on the sacral level is exceptionally rare. We describe two patients, probably the fifth and sixth ever reported. The first was a 33 year-old female who underwent surgical cord de-tethering. Surprisingly, a sacral SDAVF was discovered intraoperatively, despite negative digital subtraction angiography. The second patient was a 30 year-old male with similar pathologies. After three failed embolizations, the fistula was surgically disconnected. Both patients recovered well. A review of patients with sacral SDAVF coexisting with spinal dysraphism, with an emphasis on the basis of symptoms was done. As a rule, in these coincident disorders, the SDAVF was the direct cause of increasing symptoms. Previous reports and our findings reveal that surgery might be superior to endovascular embolization for treating sacral SDAVFs with coexisting entities, because surgery offers a one-step treatment.